Disminución de la reproducción, el crecimiento y la sobrevivencia de peces, debido a una alteración en la cantidad y la calidad del agua : reporte de caso (2006)
ABSTRACT: The authors present the problems and solutions given to an eutrophication process observed in La Vega river, at the level of the Aquatic Experimental Station of San Jose del Nus, in the province of Antioquia, Colombia. The river bed became invaded by two pasture species (Brachiaria plantaginea and Brachiaria arrecta), coming from the nearby fields. The process generated low levels of dissolved oxygen, pH changes, and high levels of dissolved carbon dioxide and organic material, among other problems. To alleviate the situation, a plan was established for the immediate, mid and long terms. The plan included recovering vegetable materials from the stream in order to prevent further pasture growth either in the stream, a downstream lake, and a connecting channel. The plan also included reforesting the river sides to eliminate the grass by excluding competition.